The frenzy - Block, Francesca Lia 1962- (HarperTeen / HarperCollins, 2010)
When she was thirteen, something terrifying and mysterious happened to Liv that she still does not understand, and now, four years later, her dark secret threatens to tear her apart from her family and her true love
Keywords: Shapeshifting / Juvenile fiction; Identity (Philosophical concept) / Juvenile fiction; Supernatural / Juvenile fiction; Werewolves / Juvenile fiction; Dysfunctional families / Juvenile fiction; Love stories